Prevalence of hepatitis B virus amongst refugees, asylum seekers and internally displaced persons in low‐ and middle‐income countries: A systematic review. Issue 1 (18th November 2022) - Lee, Caroline; Emeto, Theophilus I.; Walsh, Nick
Abstract: Hepatitis B, caused by the hepatitis B virus (HBV), is a global public health issue that affects 290 million people worldwide. Most people with hepatitis B are in low‐ and middle‐income countries (LMIC), where health systems and resources are often constrained. Refugees, asylum seekers and internally displaced persons (IDPs) often face barriers in seeking health care and are a priority population at risk of hepatitis B. No systematic review to date has evaluated the prevalence of hepatitis B amongst refugees in in LMIC. We undertook a systematic review of the literature identifying 28 studies addressing this topic. Though few studies on this topic exist, the available evidence suggests a high prevalence amongst refugees in LMIC, with wide variation between and within countries. Possible risk factors contributing to hepatitis B include unsafe injections, low immunization coverage, low awareness, mother‐to‐child transmission, and limited health services. Further study is needed to better understand the prevalence and risk factors for hepatitis B amongst refugees in LMIC, to inform public health responses. Vulnerable populations such as refugees are an important group to consider in national and global efforts to eliminate hepatitis B.